THE IMPACT OF MINIMUM WAGE ON THE LABOUR MARKET OF LITHUANIA - Karpuškienė, Vita (Ekonomika, 2011)
Recently, Lithuanian trade unions have announced the requirement for the government to raise the minimum wage by more than 10 percent, e.g. from 800 to 900 Lt. The aim of the study was to investigate the possible consequences of the implementation of such a requirement. Minimum wage (MW) macroeconomics in theoretical aspects and the practical evidence of it consequences in the EU countries are analyzed in the first part of the article. The second part provides an assessment of the impact of the 100 Lt raise in MW on the Lithuanian labor market. This assessment is carried out using econometric techniques.